Implementation Of Garbage Bank As a Means Of Increasing Community Creativity In Meranti Pandak Village - Busyro, Wahyi; Habbibullah, M.; Ruslan, Marsya Aliya Dini; Cahyono, Agung Eko Tri (Amaluna: Jurnal Pengabdian Masyarakat, 2024)
The aim of carrying out this activity is to manage and reduce plastic waste so that it does not cause damage to the surrounding environment. Apart from that, it can also increase the creativity of local residents so that plastic waste can be recycled and can become a source of income for the community. The methods used are observation, interviews and documentation. The results show that waste bank management can reduce the amount of waste so that it does not pollute the environment. By recycling plastic waste, you can certainly create a sustainable waste management system and can involve local residents in making creativity from plastic waste in order to increase income in the area. The conclusion of this research is that surrounding plastic waste can reduce damage to the environment and can provide benefits and positive impacts on the Meranti Pandak Village Community